PENGARUH ECONOMIC VALUE ADDED (EVA) DAN EARNING PER SHARE (EPS) PERUSAHAAN TERHADAP RETURN SAHAM PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ela Widasari; Mamah Mamah (The Asia Pacific Journal Of Management Studies, 2016)
Intention of this research is to know Economic Added value influence ( EVA) And Earning Per Share ( EPS) to share return at company of pharmacy which list in Effect Exchange Indonesia ( BEI).Methodologies which is used in this research of  comparability causal  that is explaining  relation  between variable.  And Method data collecting in this research through secunder data collecting and book study. In this research of  researcher use pharmacy sector manufacturing business which list in Effect Exchange Indonesia period 2011-2015 as research object. And  Population and this research sampel is 6 company which list in BEI.The hypothesis of this study is to describe not or the relationship between the Economic Value Added (EVA) and Earning Per Share (EPS) to stock return either partially or simultaneously, and the results concluded that the partial Economic Value Added (EVA) and Earning Per Share (EPS) has no effect on return shares, while simultaneously Economic Value Added (EVA) and Earning Per Share (EPS) effect on the company's stock return Pharmaceutical period 2011-2015.